2022
DOI: 10.1098/rspb.2021.1781
|View full text |Cite
|
Sign up to set email alerts
|

Large mesopelagic fish biomass in the Southern Ocean resolved by acoustic properties

Abstract: The oceanic mesopelagic zone, 200–1000 m below sea level, holds abundant small fishes that play central roles in ecosystem function. Global mesopelagic fish biomass estimates are increasingly derived using active acoustics, where echosounder-generated signals are emitted, reflected by pelagic organisms and detected by transducers on vessels. Previous studies have interpreted a ubiquitous decline in acoustic reflectance towards the Antarctic continent as a reduction in mesopelagic fish biomass. Here, we use emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…While the dissolution of the DSL in poleward waters has been previously reported in the Southern Ocean (e.g. Escobar-Flores et al, 2020;Dornan et al, 2022); the relationship of this phenomenon to environmental variables and feeding guilds has remained uninvestigated. Furthermore, the similar shift in vertical structure of larger metazoans in both hemispheres lends further support to a significant shift in the 'biological profile' of the water column.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While the dissolution of the DSL in poleward waters has been previously reported in the Southern Ocean (e.g. Escobar-Flores et al, 2020;Dornan et al, 2022); the relationship of this phenomenon to environmental variables and feeding guilds has remained uninvestigated. Furthermore, the similar shift in vertical structure of larger metazoans in both hemispheres lends further support to a significant shift in the 'biological profile' of the water column.…”
Section: Discussionmentioning
confidence: 89%
“…While the change in vertical distribution of both micronekton and plankton is clearly associated with water mass transition, we lack a mechanistic understanding of the causes of the observed differences. Previous studies have suggested that mesopelagic fish biomass in high latitude systems are restricted by latitudinal light gradients (Kaartvedt, 2008;Ljungström et al, 2021), but empirical studies have found that while backscatter typically drops off across these gradients (Norheim et al, 2016, Escobar-Flores et al, 2020, biomass of mesopelagic fish does not follow the same patterns (Escobar-Flores et al, 2020;Klevjer et al, 2020a;Dornan et al, 2022). The front between Austral and Antarctic mesopelagic structure, however, starts much closer to the equator than the front in the northern hemisphere, suggesting that photoperiod is unlikely to be the only limitation to DSL forming fish communities in polar waters.…”
Section: Discussionmentioning
confidence: 97%
“…It is unlikely that rich subpolar systems host less animal biomass than low-productive ocean gyres. We therefore believe that the subpolar decay of signal observed is related to documented latitudinal changes in the backscatter-to-biomass ratio 51 , and due to the reduction of gas-bearing organisms in subpolar sytems [52][53][54] . Because of this, the expansion of rich temperate echobiomes over subpolar echobiomes might amplify our projected biomass gains at high latitudes.…”
mentioning
confidence: 91%
“…Recently referred to as a "black box" and mechanistic nescience in our assessment of the biological pump (Hernańdez-Leoń et al, 2019), much uncertainty in active carbon estimates originates from the varying estimates of micronekton biomass (Kaartvedt et al, 2012) suggested to be underestimated by a factor of ~2.4 (Anderson et al, 2018;Dornan et al, 2022) to sometimes up to an order of magnitude (Irigoien et al, 2014). This is because biomass data are primarily collected with acoustic and/or net-sampling methods prone to selectivity and catchability biases (Kloser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that nets underestimate the actual micronekton biomass by a factor of 5-58 (Kloser et al, 2009), the bias becomes cyclical because the net data will only reflect the sampled size class, which is dependent on the net type used. Despite new sampling techniques (e.g., eDNA and optical devices), these inherent limitations have resulted in uncertain estimates of actual micronekton biomass that remain challenging to compare spatially and temporally (Dornan et al, 2022), thereby producing variable active carbon transport estimates.…”
Section: Introductionmentioning
confidence: 99%